Relationship between Effective Sentence Understanding and Achievement Motivation with Description Text Writing Skill on Google Classroom - Saddhono, Kundharu; Intan Pitaloka, Rosaliana; Devilito, Rio; Mulyaningsih, Indrya; Ketut Sudarsana, I; Isnaniah, Siti; Istanti, Wati; Septiana, Hespi (International Journal of Engineering and Technology, 2018)
This research aimed to determine the correlation between, (1) the understanding of effective sentence and writing skill in descriptive text; (2) the achievement motivation and writing skill in descriptive text; and (3) the understanding of effective sentence and achievement motivation toward writing skill in descriptive text. The research method used was a correlational survey. Population of the research is tenth grade students of Vocational High School of Surakarta with the sample consisted of 60 people were taken by simple random sampling for to analyze the data is statistic regression and correlation technique. The result of this study shows that: (1) there is a positive correlation between the understanding of effective sentence and writing skill in descriptive on google classroom; (2) there is a positive correlation between achievement motivation and writing skill in descriptive text on google classroom; and (3) there is positive correlation between the understanding of effective sentence and achievement motivation toward writing skill in descriptive text on google classroom. Considering the result of research, it can be conclude that understanding of effective sentence and achievement motivation are important factors that can improve student’s writing skill in descriptive text, however achievement motivation has bigger contribution than the understanding of effective sentence.